Scapho-metacarpal dual mobility prosthesis for TMC-1 joint salvage: technical insights - Glaser, Julia; Aman, Martin; Krohn, Thomas; Duerinckx, Joris; Panzram, Benjamin; Harhaus-Wähner, Leila (Archives of orthopaedic and trauma surgery, 2025)
Introduction - Rhizarthrosis, or osteoarthritis of the trapeziometacarpal joint, predominantly affects women over 50, with up to 30% experiencing some degree of arthritis in this joint. Traditional surgical approaches, such as trapeziectomy with ligament reconstruction, can result in some patients in persistent pain or limited functionality. TMC ball-in-socket arthroplasty, with a cup placed in the distal scaphoid, offers a promising alternative to traditional arthrodesis or resection-suspension arthroplasty. Materials and Methods - This study involved 11 patients with treated 13 hands who had persistent symptoms after previous TMC-1 surgeries. Procedures included a bilateral scaphometacarpal implantation in two cases. Main symptoms were pain, thumb shortening, and reduced grip strength. The Touch® ball-in-socket prosthesis was used, with specific considerations for implant selection, surgical steps and customization based on the patient-specific case. Results - We included 11 patients with 13 thumbs, with a mean follow-up time of 16 months (range: 4–49 months). All patients showed significant improvements in thumb function. Grip strength, as measured by dynamometry, showed an aver-age recovery to 80–90% of the contralateral side. Thumb opposition according to the Kapandji score averaged 9 out of 10. Radiographs demonstrated good osseointegration of the implants, with no signs of prosthetic loosening or dislocation. Complications included one case of persistent mild hypesthesia of the radial nerve’s superficial branch, which did not impair function, and one scaphoid fracture 4 weeks post-implantation during cast immobilization. Conclusion - The scapho-metacarpal dual mobility prosthesis is a feasible and effective option for patients with persistent TMC-1 symptoms after failed surgeries. It uniquely preserves both thumb mobility and length, unlike alternatives like arthrodesis and tendon suspensionplasty, which remain options if the prosthesis fails. Further research and long-term studies are necessary to determine the definitive role of this approach in complex TMC-1 cases.